Simplified method for estimating settlement of disconnected piled raft foundations based on a finite element approach using interaction factors - Boyoung Yoon; Changho Lee (Scientific Reports)
Abstract Disconnected piled raft foundations (DPRF) have been developed to reduce the number of piles and avoid stress concentrations at pile heads by placing a cushion layer between the raft and piles. Although this cushion decouples the direct raft-pile interaction, its effectiveness in reducing settlement remains controversial. This study evaluates the settlement of the foundation with cushion layer using a three-dimensional finite element model, varying the cushion properties (i.e., thickness and elastic modulus) and the pile configurations (i.e., number, spacing, and length). The results were compared with those of the raft on the cushion and the group pile foundation, to clarify the effect of the raft-cushion-pile interaction within the serviceability settlement range. The findings demonstrate that the settlement of DPRF is governed by the relative rigidity between piled subsoil and cushion, and interactions among raft—cushion—group piles. This study introduces a new factor X DPRF to quantitatively evaluate the governing factors and incorporates it into the stiffness estimation formula. The proposed formula accounts for both the stiffness ratio between a group pile foundation and raft on cushion (k GPF /k R-CN ) and pile—cushion contact characteristics. The proposed method is validated using experimental and numerical data from previous studies. This study offers a practical tool for estimating k DPRF and provides insights to address the debate on the role of cushion layers in the settlement reduction.